Should surgery be delayed in patients taking direct oral anticoagulants who suffer a hip fracture? A retrospective, case-controlled observational study at a UK major trauma centre. Issue 4 (28th April 2018) - Mullins, Barry; Akehurst, Harold; Slattery, David; Chesser, Tim
Abstract : Objective: To determine whether not waiting for the elimination of direct oral anticoagulants (DOACs) has an effect on the amount of perioperative bleeding in patients who undergo operative treatment of a hip fracture. Design: Observation, retrospective case–control study. Setting: A single UK major trauma centre. Participants: Patients who sustained a hip fracture were identified using the National Hip Fracture Database (NHFD). All those found to be taking a DOAC at the time of fracture were identified (n=63). A matched group not taking a DOAC was also identified from the NHFD (n=62). Main outcome: Perioperative drop in haemoglobin concentration. Results: There was no relationship between admission to operation interval and perioperative change in haemoglobin concentration in patients taking DOACs (regression coefficient=−0.06 g/L/hour; 95% CI −0.32–0.20; p=0.64). No relationship was found between the time from admission to operation interval and the probability of transfusion (OR=0.94; 95% CI 0.85 to 1.90; p=0.16) or reoperation (OR=1.04; 95% CI 0.93 to 1.16; p=0.49). One mortality was recorded in the DOAC group within 30 days of admission, and this compared with five in the matched group of patients (p=0.2). Conclusions: Delaying surgery in patients who sustain a hip fracture who are taking a DOAC drug has not been shown to reduce perioperative bleeding or affect their mortality in this study.